Regional links of good governance in rural space - Káposzta, József (Studia Mundi – Economica, 2018)
Preparing strategies of rural economy, planning has found a new meaning nowadays as several new factors have entered the perspective of analyses by the penetration of globalization. We have also recognised that within a given region the economic changes are partly determined by outside factors nowadays - these changes are not influenced by the performers within the region itself -, and are partly determined by the decisions and activities of the local performers. All these links can illustrate well that a combined system of relationships of several inside and outside factors are necessary for the development, for the operation and for the improvement of good governance. The present paper deals with the following questions: what direction of change is desired for the development of good governance; is the change inevitably necessary and what can be the most important goals of regional economic policy, which can help the improvement of good governance in rural space?